Safety assessment of condensed phosphate intake from fishery and processed marine food products in Korea with respect to gender, age, and region. (24th April 2021) - Kim, Hyung Soo; Jang, Dae Yong; Koo, Ye Ji; Pack, Eun Chul; Lee, Seung Ha; Choi, Dal Woong
Abstract: Condensed phosphates are used as food additives, especially in marine products and meat, to improve food quality. The import and consumption of fishery and processed marine food products in Republic of Korea have reportedly increased by ~5 per cent annually. However, processed marine food products are often intentionally adulterated with excessive amounts of condensed phosphates to increase their weight. Excessive intake of condensed phosphates via consuming processed marine food products can lead to various adverse effects on human health due to anionic imbalance. Herein, we conducted a safety assessment of condensed phosphates in 14 types of fishery and processed marine food products in Korea for the first time. Subgroup analysis of various factors including gender, age, and region was also performed, and the risk level of exposure for each group was estimated. Safety assessments by age and gender indicated that infants were at the highest risk. In the regional safety assessment, Chungnam, the most inland region, showed the lowest risk. For both the general and the high-intake groups (95th percentile) in all classifications, the risk was lower (<20 per cent) than the international standard, and the phosphorus content of the 14 types of processed marine products in Korea was confirmed to be safe for human consumption. Graphical Abstract: